Vitamin D-gene interactions in multiple sclerosis. - Berlanga-Taylor, A; Disanto, G; Ebers, G; Ramagopalan, S (2011)
Vitamin D has been studied for over a century and its functions related to calcium homeostasis are well established. Over the last 30 years or so it has become increasingly clear that it has a wider role in physiology and, importantly, also in disease. Vitamin D deficiency has been linked to multiple sclerosis (MS); however the molecular mechanisms of this association were poorly understood. Recent technological advances have provided major insights as to how vitamin D may exert its role, particularly through the actions of the vitamin D receptor (VDR). In this review we aim to highlight the importance of the interaction between vitamin D and MS associated genes which provide a biological basis for the association between vitamin D and MS risk.